PENGARUH VARIABEL KEPEMIMPINAN, KOMUNIKASI, KEKUASAAN TERHADAP KOMITMEN KARYAWAN - Mei Ie; Henny Henny; Nicolas Harifin (PROSIDING SERINA, 2021)
Employee commitment is the degree to which an employee identifies with the company and its goals and wishes to maintain membership in the company. In an organization, there are several variables that are thought to affect the commitment of employees including communication variables, leadership variables and power variables. The purpose of this study was to determine the influence of leadership variables, communication variables and power variables on employee commitment. The sampling technique used was purposive sampling. The research sample used is 62 people who are permanent employees and contract employees who work at PT XYZ. Based on the results of hypothesis testing, it shows that leadership, communication, and power have an effect on employee commitment.